2012
DOI: 10.1177/070674371205700209
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic Distress and the Course of Posttraumatic Stress Disorder Symptoms: A Meta-Analysis

Abstract: Objective: To examine how peritraumatic distress modulates the severity of posttraumatic stress disorder (PTSD) according to the timing of the PTSD symptom assessments. Method:A systematic literature review of English-and French-language studies having administered the Peritraumatic Distress Inventory (PDI) was conducted. Meta-analyses were performed on correlations relating PDI and PTSD symptom scores obtained from the sampled studies. The meta-analyses, which included calculations of regression slopes, took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 33 publications
4
78
0
2
Order By: Relevance
“…The importance of PD in predicting PTSD among these Palestinian children concurs with adult survivors of war and peace-time traumas (Lensvelt-Mulders et al, 2008; Thomas et al, 2012) but differs from some findings among children exposed to single peace-time trauma (Dalgleish et al, 2008). The importance of PD as a severe risk for PTSD symptoms among war-affected Palestinian children may lie in the chronicity of life threat and adversities.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The importance of PD in predicting PTSD among these Palestinian children concurs with adult survivors of war and peace-time traumas (Lensvelt-Mulders et al, 2008; Thomas et al, 2012) but differs from some findings among children exposed to single peace-time trauma (Dalgleish et al, 2008). The importance of PD as a severe risk for PTSD symptoms among war-affected Palestinian children may lie in the chronicity of life threat and adversities.…”
Section: Discussionmentioning
confidence: 82%
“…Research suggests pre-, peri-, and post-trauma responses to be decisive for the development of PTSD (Olff et al, 2015), with acute stress disorder (ASD) and peritraumatic dissociation (PD) playing an important role (Kassam-Adams et al, 2012). Among adults there is evidence about PD predicting PTSD (for a meta-analysis, see Lensvelt-Mulders et al, 2008; Ozer, Best, Lipsey, & Weiss, 2003), especially in the short run (Thomas, Saumier, & Brunet, 2012; van der Velden & Wittman, 2008). Yet, among children and adolescents evidence is very limited and findings are inconclusive, as some research among young vehicle-accident survivors has confirmed that PD forms a severe risk for PTSD (Bui et al, 2010), while others showed minor importance (Dalgleish et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Peritraumatic distress (PDI) refers to emotional and physical stress responses that occur during or immediately after the traumatic event (Thomas, Saumier, & Brunet, 2012). It primarily involves the perception that one's life in endangered as well as the presence of negative emotions such as fear, horror, helplessness, shame and anger.…”
Section: Introductionmentioning
confidence: 99%
“…The traumatic stress literature shows that peritraumatic reactions play a key role in the development of longer term PTS: distress during or immediately after a traumatic event can predict the development of PTSD symptoms, and dissociation can predict symptom persistence (Brunet et al, 2001;Thomas et al, 2012). However, there is some debate about the strength and nature of this relationship.…”
Section: Prenatal Maternal Stress and Child Motor Development [57]mentioning
confidence: 99%
“…Exposure to a potentially traumatic event can trigger immediate (peritraumatic) reactions of distress or dissociation, and these can predict subsequent posttraumatic stress (Brunet, Weiss, Metzler, Best, & et al, 2001;Thomas, Saumier, & Brunet, 2012). For example, Nishi et al (2010) found that motor vehicle accidents predicted peritraumatic distress, which in turn predicted PRENATAL MATERNAL STRESS AND CHILD MOTOR DEVELOPMENT [37] ongoing posttraumatic stress symptoms.…”
Section: The Relationship Between Different Types Of Stressmentioning
confidence: 99%